Anti-ribosomal P antibody: A multicenter study in childhood-onset systemic lupus erythematosus patients - Valões, C. C.M.; Molinari, B. C.; Pitta, A. C.G.; Gormezano, N. W.S.; Farhat, S. C.L.; Kozu, K.; Sallum, A. M.E.; Appenzeller, S.; Sakamoto, A. P.; Terreri, M. T.; Pereira, R. M.R.; Magalhães, C. S. [UNESP]; et al. (SAGE Publications, 2017)
Objectives Anti-ribosomal P protein (anti-P) autoantibodies are highly specific for systemic lupus erythematosus (SLE). However, the evaluation of this autoantibody in childhood-onset SLE (cSLE) populations has been limited to a few small series, hampering the interpretation of the clinical and laboratorial associations. Therefore, the objective of this multicenter cohort study was to evaluate demographic, clinical/laboratorial features, and disease damage score in cSLE patients with and without the presence of anti-P antibody. Methods This was a retrospective multicenter study performed in 10 pediatric rheumatology services of São Paulo state, Brazil. Anti-P antibodies were measured by ELISA in 228 cSLE patients. Results Anti-P antibodies were observed in 61/228 (27%) cSLE patients. Frequencies of cumulative lymphadenopathy (29% vs. 15%, p = 0.014), acute confusional state (13% vs. 5%, p = 0.041), mood disorder (18% vs. 8%, p = 0.041), autoimmune hemolytic anemia (34% vs. 15%, p = 0.001), as well as presence of anti-Sm (67% vs. 40%, p = 0.001), anti-RNP (39% vs. 21%, p = 0.012) and anti-Ro/SSA antibodies (43% vs. 25%, p = 0.016) were significantly higher in cSLE patients with anti-P antibodies compared to those without these autoantibodies. A multiple regression model revealed that anti-P antibodies were associated with autoimmune hemolytic anemia (odds ratio (OR) = 2.758, 95% confidence interval (CI): 1.304-5.833, p = 0.008) and anti-Sm antibody (OR = 2.719, 95% CI: 1.365-5.418, p = 0.004). The SLICC/ACR damage index was comparable in patients with and without anti-P antibodies (p = 0.780). Conclusions The novel association of anti-P antibodies and autoimmune hemolytic anemia was evidenced in cSLE patients and further studies are necessary to determine if anti-P titers may vary with this hematological manifestation.
Keywords: anti- ribosomal P protein antibodies; autoimmune hemolytic anemia; childhood; neuropsychiatric lupus; Systemic lupus erythematosus